Burkina Faso's Perspective on Total Official Support for Sustainable Development (TOSSD) - Delalande, Guillaume (OECD Development Co-operation Working Papers, 2020)
This working paper presents the main findings of the pilot study conducted in Burkina Faso in 2019 as part of the development of the statistical measurement framework for "Total Official Support for Sustainable Development (TOSSD)". The pilot study includes Burkina Faso's perspective on the statistical methodology of TOSSD, first orders of magnitude of TOSSD to Burkina, as well as a statistical capacity assessment of Burkina Faso to access, collate, collect, analyse and use data on external financing in support of sustainable development